A cross-sectional bibliometric analysis of care phases in SCImago’s top five intensive care journals in 2012 and 2022 - Tan, Mark Z. Y.; Lim, Pei Shan; Shiralkar, Saarth; Liu, Bruce; Scott, Laura; Palethorpe, Matthew; Dark, Paul; Hansel, Jan (Frontiers in Medicine, 2025)
BackgroundThe critically ill patient’s journey can broadly be divided into three phases; events prior to admission, during the ICU stay, and following discharge. There is a paucity of evidence on what proportion of research outputs in high-impact intensive care journals address the respective phases. We aimed to investigate how intensive care research published in SCImago’s top five journals mapped onto phases of care and the National Institute of Health and Care Research James Lind Alliance (NIHR JLA) Priority Setting Partnership research topics over a decade. The study was prospectively registered with the Open Science Framework https://osf.io/r8vs5/.MethodsWe conducted a bibliometric cross-sectional analysis of intensive care research published in 2012 and 2022, in the top five intensive care journals according to the SCImago ranking system. We categorised studies according to phases of care: “pre-ICU”, “in ICU”, “post-ICU”, or “multiple phases”; and according to the previously published NIHR JLA research topics. We adhered to relevant PRISMA and BIBLIO reporting guidelines in conducting the review.ResultsIn 2012 and 2022, respectively, 755 (73%) and 602 (73.7%) studies were focused on the “in ICU” phase, 148 (14.3%) and 87 (10.6%) studies on the “pre-ICU” phase, and 39 (3.8%) and 56 (6.9%) studies on the “post-ICU” phase. In both years, two NIHR JLA research topics were most represented: “respiratory/ventilation” (19.1% and 26.6% in 2012 and 2022, respectively) and “infection/sepsis” (15.6% and 13.7% in 2012 and 2022, respectively).ConclusionAmong the top five intensive care journals according to the SCImago ranking system, research tends to be centred on the period during patients’ ICU stay, and characterised most by the topics of “respiratory/ventilation” and “infection/sepsis.”